2014
DOI: 10.1590/s0104-12902014000400018
|View full text |Cite
|
Sign up to set email alerts
|

Sexualidade e câncer de mama: uma revisão sistemática da literatura

Abstract: ResumoO objetivo deste estudo foi compreender como o cân-cer de mama e seus tratamentos afetam a vivência da sexualidade da mulher acometida. Foi realizada uma revisão sistemática qualitativa de artigos científicos, publicados entre 2000 e 2010, disponíveis nas bases de dados PubMed, Web of Science, LILACS e SciELO. Foram obtidos 50 artigos cujos textos foram categorizados segundo análise de conteúdo temática. Foram identificadas seis categorias temá-ticas: a cirurgia mamária e os demais tratamentos para o cân… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
20

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 55 publications
0
14
0
20
Order By: Relevance
“…20 Sexuality changes during life, especially when a disease such as breast cancer arises because it is a multidimensional phenomenon involving psychological, physical, cultural and social factors, and their treatment causes important temporary and permanent sequels. 21 The negative consequences that the removal of a tumor can have are associated, mainly to the body image and perception of sexuality, and the result can be perceived as mutilation, persisting even after the breast reconstruction. 22 Patients with breast cancer suffer from reduced Cognitive Function 23 linked to memory and concentration function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Sexuality changes during life, especially when a disease such as breast cancer arises because it is a multidimensional phenomenon involving psychological, physical, cultural and social factors, and their treatment causes important temporary and permanent sequels. 21 The negative consequences that the removal of a tumor can have are associated, mainly to the body image and perception of sexuality, and the result can be perceived as mutilation, persisting even after the breast reconstruction. 22 Patients with breast cancer suffer from reduced Cognitive Function 23 linked to memory and concentration function.…”
Section: Discussionmentioning
confidence: 99%
“…13 There was a decrease in this dimension; authors claim that there is a process of reformulation and (re) elaboration after breast cancer, and it is difficult to even after placement of prosthesis. 21,22,25 The decrease in this dimension is significantly associated with depression. 25 The study found higher scores in the Body Image when married, older, literate, housewife patients with a diagnosis of fewer than 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Há piora na qualidade de vida das mulheres que relatam dores, incapacidades funcionais, náuseas, vômito, fadiga, disfunção cognitiva, além de muitas vezes passarem por falência ovariana e mudanças na função sexual induzidas pela quimioterapia (SANTOS et al, 2014(SANTOS et al, , p. 1342(SANTOS et al, -1355. No entanto, mulheres com câncer de mama que tem um maior nível de religiosidade e espiritualidade apresentavam melhor qualidade de vida.…”
Section: Discussionunclassified
“…Dessa forma, o câncer afeta as diversas atividades desempenhadas pela mulher, dentre elas a de parceira sexual. Essas vivências são explicitadas por M07 e M03 e ratificadas pelo estudo de Santos et al (2014), os quais identificaram que o câncer envolve um comprometimento radical na sexualidade feminina por induzir à menopausa precoce, diminuição da lubrificação vaginal e diminuição do desejo sexual, que interferem na relação conjugal (15) : Esse tratamento mexe muito com o corpo todo, mexe com a vagina, mexe com o intestino, ele mexe com muita coisa... às vezes, penso que a mulher não fala que está doendo, porque quando a mulher responde na cama é uma coisa, agora, quando não pode, é outra (M07).…”
Section: (M07)unclassified